Effects of change in population, household conditions and farming practices on agricultural land use in the Volta River basin of Ghana, 1984-2000 - Codjoe, Samuel N. A.; Ehlers, Eckart; Vleck, Paul L. G. (ERDKUNDE, 2005)
The Volta River basin in Ghana, which covers about 160,000 km², is one of the most economically deprived areas in West Africa. Rain-fed and some irrigated agriculture is the main economic activity of the majority of the population living in this region. Rapid population growth and low economic standards of living have brought in their wake a lot of consequences for agricultural land resources in this region. This paper hypothesises that population growth, general improvement in household conditions and improved inputs for farming has increased agricultural land utilisation in two agro-ecological zones (derived and dry savannahs) of the Volta River basin in Ghana between 1984 and 2000. The results show that land fallow was practised widely in 1984 but not in 2000 in the dry savannah zone. Secondly, there has been population pressure on agricultural land use since 1984 in the derived savannah zone. Thirdly, improvements in household conditions and affluence have not increased agricultural land use. Finally, even though innovations in mechanised farming had spread to the derived savannah zone, it has not increased agricultural land utilisation. In the dry savannah zone simple subsistence forms of organic farming were still being practised.